Lost in translation? Information quality in pediatric pre-hospital medical emergencies with a language barrier in Germany - Frank Müller; Dominik Schröder; Jennifer Schäning; Sybille Schmid; Eva Maria Noack (BMC, 2023)
Abstract Background In pediatric medical emergencies, paramedics and emergency physicians must often rely on the information of third parties, often caregivers, to gather information. Failing to obtain relevant information may lead to misinterpretation of symptoms and subsequent errors in decision making and clinical treatment. Thus, children and/or caregivers with limited proficiency of the locally spoken language may be at risk for medical errors. This study analyzes logs of rescue missions to determine whether paramedics could obtain essential information from German-speaking and foreign-language children and their caregivers. Methods We conducted a secondary data analysis based on retrospective data on pediatric patients of four emergency medical services (EMS) stations in Northern Germany. We defined language discordance with communication difficulties as main exposure. We used documentation quality as outcome defined as existing information on (a) pre-existing conditions, (b) current medication, and (c) events prior to the medical emergency. Statistical analyses include descriptive statistics, simple regression and multivariable regression. As multivariable regression model, a logistic regression was applied with documentation quality as dependent variable and language discordance with communication difficulties as independent variable adjusted for age, sex and Glasgow Coma Scale (GCS). Results Data from 1,430 pediatric rescue missions were analyzed with 3.1% (n = 45) having a language discordance with communication difficulties. Patients in the pediatric foreign-language group were younger compared to German-speaking patients. Thorough documentation was more frequent in German-speaking patients than in patients in the foreign-language group. Pre-existing conditions and events prior to the medical emergency were considerably more often documented in German-speaking than for foreign-language patients. Documentation of medication did not differ between these groups. The adjustment of sex, age and GCS in the multivariable analysis did not change the results. Conclusion Language barriers are hindering paramedics to obtain relevant information in pediatric pre-hospital emergencies. This jeopardizes the safe provision of paramedic care to children who themselves or their caregivers are not fluent in German language. Further research should focus on feasible ways to overcome language barriers in pre-hospital emergencies. Trial registration This is a retrospective secondary data analysis of a study that was registered at the German Clinical Trials Register (No. DRKS00016719), 08/02/2019.